PENERAPAN PENDEKATAN SCIENTIFIC MENGGUNAKAN GUIDED INQUIRY PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VIII - Fariska Murtina Sari (MEJ (Mathematics Education Journal), 2017)
The purposes of this research were to describe the implementation of scientificapproach used guided inquiry, student’s learning activities, student’s critical thinking skills in teaching and learning mathematic. This type of research is a descriptive research, with quantitative and qualitative approaches. A method in collecting the data used two instruments including observation, and test. The data were obtained from 32 students in class VIII-2 SMP Negeri 3 Malang. The results showed that the implementation scientific approach used guided inquiry in teaching and learning mathematic can be implemented in accordance with the learning steps which have been prepared with an average of 82,39 teacher activity and 78,13 the learners activities. The activity of learners during the learning process is good category, with details of the activity of observing, reasoning, trying and communicate indicate same category, which is good, whereas asking activity indicate good enough category. The whole ability of students critical thinking skills are very good, with with the acquisition of which is high on the aspects identifying assumptions given, and indicate good category with revealing indicator data/definition/theorem to solve problems and evaluation aspects to solve problems.